İdarenin kusursuz sorumluluğu -eleştirel yaklaşım- - Yayla, Ahmet (İstanbul Bilgi Üniversitesi, 2006)
İdarenin sorumluluğu öğreti ve mahkeme içtihatlarında kusurlu sorumluluk ve kusursuz sorumluluk olmak üzere ikiye ayrılmaktadır. Çalışmada, kusursuz sorumluluğun geçerli olacağı alanı tespit edebilmek için öncelikle kusurlu sorumluluğun yani hizmet kusurundan sorumluluğun ne anlama geldiği üzerinde durulmuştur. İdarenin kusursuz sorumluluğunu açıklamak içinse, Türk ve Fransız Öğretisinde ve İçtihatlarında kullanılan belirli ilke ve kavramlar incelenmiştir. İdarenin kusursuz sorumluluğunu açıklayan ilkelerin uygulandığı İdari Yargı Kararlarının irdelenmesi sonucunda,?eylem ile zarar arasında nedensellik bağı kurulmasının bazı hallerde güçlük teşkil ettiğinin görülmesi, sorumluluk hukukuna ilişkin önemli bir sorun olarak ortaya çıkmaktadır. İdarenin kusursuz sorumluluğu ile ilgili yargı kararları incelendiğinde, İdare Hukukunda sorumluluğa esas teşkil eden ilkelerin başkalaşım geçirdikleri söylenebilecektir. Bu başkalaşım, çalışmanın ilk bölümünde, idari yargı kararları ışığında klasik kusursuz sorumluluk kurgusunu sorgulamayı gerektirmiştir. İkinci bölümde ise, böyle bir sorgulama sonucunda, klasik kurgunun bozulması ihtimali irdelenmektedir.

According to the doctrine and jurisprudence of administrative law, the responsibility of the administration for the consequences of its action may either be with or without fault. The responsibility of the administration with fault (fault in public service) was taken basis in order to determine the area of the responsibility of the administration without fault. Two major theories are applied by the Turkish and French Supreme Administrative courts which establish the responsibility of the administration without fault: The Theory of Risk and The Rupture of Equality, both of which were examined in this research. The difficulties that are seen from time to time, while establishing the relation between the act and the damage, which can be witnessed in administrative case law concerning the principles of the responsibility without fault, constitutes one of the major problems in responsibility law. Thus, it can be said that the principles that form the essence of the responsibility of the administration can not be defined by traditional means. It is for this that these concepts have evolved and will continue evolving. This evolution necessities one to question, taking in to account the administrative law jurisprudence, the traditional doctrine of responsibility law. Then, after having achieved this analysis, one must look in to the possibility that this traditional construct should be abandoned.